EFEKTIVITAS PELAKSANAAN FUNGSI LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN DI KELURAHAN AIR HITAM KECAMATAN PAYUNG SEKAKI - sari, Rini Mustika; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study examines the Effectiveness of the implementation of Lembaga Pemberdayaan Masyarakat Kelurahan (LPMK) functions at Air Hitam Village, Payung Sekaki District, Pekanbaru. This study is a descriptive study which is aimed to see the effectiveness of LPMK Air Hitam in actuating its function in the society. This study was based on the result of interview and observation as the writer’s initial data which found indications of problems; the persistence of the development program that has not been realized, lack of community participations, and less activation of LPMK management. The writer used the theory of Richard M. Steers which consists of, ability to adapt, work productivity, job satisfaction, and resource utilization. The writer obtained the data through literature review and field study (observation and interview). The conclusion of this study shows that the function of LPMK at Air Hitam village is not effective yet. In compiling the aspirations of society, LPMK has been able to accommodate, formulate, and convey the aspirations of society in development through Musrenbang. But, the ability of resources of LPMK management is still low and the participation of the society in giving proposal and ideas is still passive. Key Words : The Effectiveness, Functions, LMPK.